Karakterisasi Endapan Maar Ranu Segaran, Ranu Agung, dan Ranu Katak Serta Evolusi Magma Pembentuk Maar Di Kecamatan Tiris, Kabupaten Probolinggo, Jawa Timur Oleh: - , Brilian Budi Prakosa ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Maar-diatrem is a volcanic feature that is sought-after and advantageous in mineral and geothermal exploration, as it gives a clear evidence of the presence of hydrothermal system which potentially yields mineralization and geothermal energy. Mount Lamongan has been defined as the area where numerous maar volcanoes exist. The objectives of this study are: to interprete geological condition of research area